2018
DOI: 10.1016/j.ando.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor modulators

Abstract: The glucocorticoid hormone cortisol acts throughout the body to support circadian processes and adaptation to stress. The glucocorticoid receptor is the target of cortisol and of synthetic glucocorticoids, which are used widely in the clinic. Both agonism and antagonism of the glucocorticoid receptor may be beneficial in disease, but given the wide expression of the receptor and involvement in various processes, beneficial effects are often accompanied by unwanted side effects. Selective glucocorticoid recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(119 citation statements)
references
References 53 publications
(55 reference statements)
7
112
0
Order By: Relevance
“…3,4 The HPA axis, highly involved in the stress response, triggers the adrenal cortex to release GC. 11 In an acute pathomimetic model of AD obtained after a single intracerebroventricular (icv) injection of an oligomeric solution of Aβ (oAβ [25][26][27][28][29][30][31][32][33][34][35], [12][13][14] we demonstrated a strong, long-lasting activation of the HPA axis, associated with a modification of GR and MR expression in brain regions involved in the control of GC secretion (hippocampus, amygdala, and hypothalamus), 15 supporting its involvement in the etiology of AD. 5 GC are necessary for normal cellular activity and fundamental for many CNS functions, including learning and memory.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…3,4 The HPA axis, highly involved in the stress response, triggers the adrenal cortex to release GC. 11 In an acute pathomimetic model of AD obtained after a single intracerebroventricular (icv) injection of an oligomeric solution of Aβ (oAβ [25][26][27][28][29][30][31][32][33][34][35], [12][13][14] we demonstrated a strong, long-lasting activation of the HPA axis, associated with a modification of GR and MR expression in brain regions involved in the control of GC secretion (hippocampus, amygdala, and hypothalamus), 15 supporting its involvement in the etiology of AD. 5 GC are necessary for normal cellular activity and fundamental for many CNS functions, including learning and memory.…”
Section: Introductionmentioning
confidence: 67%
“…These steroid hormones readily cross the BBB and bind to low-affinity glucocorticoid receptors (GR) and high-affinity mineralocorticoid receptors (MR). 9,[16][17][18][19] We also observed that an antagonist and selective modulators of the GR could potently counteract the effects of oAβ [25][26][27][28][29][30][31][32][33][34][35] injection in the hippocampus, arguing strongly for a therapeutic potential of modulating GR activity. 6 While MR are localized mainly in the hippocampus, GR are more ubiquitous and are particularly found in several structures of the limbic system (prefrontal cortex [PFC], hippocampus, and amygdala), which are strongly involved in cognitive and psychological functions but also are important components of the neural circuitry modulating HPA axis activity.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations